2021
DOI: 10.21608/ejchem.2021.82036.4053
|View full text |Cite
|
Sign up to set email alerts
|

Volatile and Non-Volatile Chemical Compounds and Biological Power of the genus Lavandula: Case of two Moroccan Lavenders Lavandula angustifolia Mill. (Cultivated Lavander) and Lavandula pedunculata (Mill.) Cav. (Spontaneous Lavander)

Abstract: Volatile and Non-Volatile Chemical Compounds and Biological Power of the genus Lavandula: Case of two Moroccan Lavenders Lavandula angustifolia Mill. (Cultivated Lavender) and Lavandula pedunculata (Mill.) Cav.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…Likewise, linaool acetate, a primary constituent of L. abrialis EO, has a very substantial correlation with strain growth inhibition of E. cloacae and S. aureus. These results corroborate with previous studies including Radi et al (2022) who showed that L. stoechas EOs demonstrated significant antibacterial activity against several strains, such as S. aureus, Staphylococcus typhi, E. coli, A. baumanii, E. Cloacae and Staphylococcus dysenteria and antifungal activity against Candida glabrata, Candida albicans, Candida spp., Aspergillus fisheri, and Fusarum solani. According to Dorman and Deans, (2000), the antibacterial activity was brought on by the presence of phenol (1,8 cineole), alcohols (cubenol, borneol, terpineol, etc.…”
Section: Correlation Between the Chemical Composition Of The Eos Stud...supporting
confidence: 92%
See 2 more Smart Citations
“…Likewise, linaool acetate, a primary constituent of L. abrialis EO, has a very substantial correlation with strain growth inhibition of E. cloacae and S. aureus. These results corroborate with previous studies including Radi et al (2022) who showed that L. stoechas EOs demonstrated significant antibacterial activity against several strains, such as S. aureus, Staphylococcus typhi, E. coli, A. baumanii, E. Cloacae and Staphylococcus dysenteria and antifungal activity against Candida glabrata, Candida albicans, Candida spp., Aspergillus fisheri, and Fusarum solani. According to Dorman and Deans, (2000), the antibacterial activity was brought on by the presence of phenol (1,8 cineole), alcohols (cubenol, borneol, terpineol, etc.…”
Section: Correlation Between the Chemical Composition Of The Eos Stud...supporting
confidence: 92%
“…Indeed, camphor which is a major compound of the two studied EOs (24.35% for L. stoechas and 11.24% for L. abrialis), presented a strong correlation with the antioxidant activity, which was confirmed by the results of the heat map. Previous studies have confirmed that this compound also has strong antioxidant activity (Radi et al, 2022;Laib, 2012). Additionally, to camphor's particular antioxidant properties, the synergistic interactions that can be established between the different constituents of essential oil were also behind its considerable antioxidant power (Laib and Barkat, 2011;Radi et al, 2022;Laib, 2012;Fatiha et al, 2011).…”
Section: Antioxidant Activity Of Essential Oils By the Dpph Anti-radi...mentioning
confidence: 78%
See 1 more Smart Citation